Technology-based learning effect on the learning outcomes of Indonesian students: a meta-analysis - Iqbal Faza Ahmad; Farida Agus Setiawati; Rani Putri Prihatin; Qonitah Faizatul Fitriyah; Zulkifli Syauqi Thontowi (International Journal of Evaluation and Research in Education (IJERE), 2024)
The utilization of information technology in education offers learners access to a variety of learning resources that are not restricted. It is expected that this use will enhance the success of the learning process and the attainment of educational goals. The purpose of this study is to examine the impact of information technology-based learning on the academic performance of students in Indonesia. This research adopts a meta-analysis design and utilizes a selection process based on established criteria to gather studies from the Google Scholar and Scopus databases. The study adheres to the PRISMA protocol. There were 51 studies included, comprising 44 academic journals and seven proceedings. The analysis technique applied is a meta-analysis using the random effect size model. The results of this study indicate that the utilization of information technology in education has a significant impact on the learning achievement of Indonesian students. The analysis of 51 studies, including 44 scientific journals and seven proceedings, showed that the effect sizes of the studies varied from -0.80 to 5.85, indicating heterogeneity in the studies analyzed. The effect size model used in this meta-analysis was a random effect size model, with the summary effect value showing a large effect size with a value of 1.285, a p-value<0.001, and a confidence interval ranging from 1.012 to 1.559. Subgroup analysis also revealed a significant difference in the average effect size across different levels of education, including elementary, secondary, and tertiary education. The results of the study showed no evidence of publication bias.